The result of the influence of center pivot irrigation machine operations on rain (irrigation) intensity (Mongolian Journal of Agricultural Sciences, 2021)
The water consumption through the nozzle or water pressure through the nozzle at the given water thickness (У,min) the two technological parameters, the pressure of  the nozzle (X1, PSI) and the rotational speed of the nozzle (X2, m/min) are used to determine the state of the impact at 8 mm nozzle. The experiment was determined under laboratory conditions on a Low Energy Nozzle (LEN). The experiment was conducted in the ‘’ Irrigation machinery and  equipment design’’ laboratory of the School of Engineering and Technology of the MULS using the ‘’Low pressure nozzle distribution radius and rain intensity measuring equipment’’.  The maximum intensity of water supplied by the nozzle is 1.727 mm / min or the maximum pressure is 30 PSI and the minimum flow rate is 0.313 mm / min. The pressure regulator at 20 min was at a value of 20 PSI, and the transition speed was at a maximum of 3 m / min.Бороожуулах эрчимд машины ажиллах горим нөлөөлөх байдлыг тодорхойлсон дүнБороожуулах хошуугаар өгч байгаа усны зарцуулгын хэмжээ буюу өгсөн усны зузаанд (Y, мм) хошуугаар гарах усны даралт , машины тойрох хурд   гэсэн технологийн хоёр параметр дангаараа болон хавсран үзүүлэх нөлөөллийн төлвийг  тодорхойлох туршилтыг 8 мм голчтой бороожуулах хошуун дээр лабораторийн нөхцөлд тодорхойлов. ХААИС-ийн ИТС-ийн “ Усалгааны машин, тоног төхөөрөмжийн хийц “лабораторт 2019 онд “Бороожуулах хошууны борооны эрчим, усны жигд тархалт тодорхойлох төхөөрөмж”- ийг ашиглан туршилтыг хийж гүйцэтгэв. Нам даралтат бороожуулах хошууны борооны эрчмийг  тодорхойлж, үр дүнг математик статистикийн аргаар боловсруулахад бороожуулах хошуугаар өгч буй усны хамгийн их хэмжээ 1.727 мм/мин нь даралт хамгийн их 30 PSI, шилжих хурд хамгийн бага 1м/мин үед байгаа бол хамгийн бага хэмжээ  0.313 мм/мин нь даралт тохируулагч 20 PSI утга дээр, шилжих хурд хамгийн их буюу 3 м/мин байв. Түлхүүр үг: Даралт тохируулагч, бороожуулах хошууны жигд тархалт, нам даралтат бороожуулах хошуу